Benefits and tradeoffs of reduced tillage and manure application methods in a Zea mays silage system - Dittmer, Kyle M; Darby, Heather M.; Goeschel, Tyler R; Adair, E. Carol (Wiley, 2020)
A critical question is whether there are agricultural management practices that can attain the multiple management goals of increasing yields, preventing nutrient losses, and suppressing greenhouse gas (GHG) emissions. No‐till and manure application methods, such as manure injection, can enhance nutrient retention, but both may also enhance emissions of nitrous oxide (N2O), a powerful GHG. We assessed differences in soil N2O and carbon dioxide (CO2) emissions, nitrate and ammonium retention, and crop yield and protein content under combinations of vertical‐till, no‐till, manure injection, and manure broadcast without incorporation in a corn (Zea mays L.) silage system. During the growing seasons of 2015–2017, GHG emissions and soil mineral nitrogen (N) were measured every other week or more frequently after management events. Crop yield and protein content were measured annually at harvest. No‐till reduced CO2 emissions but had no impact on N2O emissions relative to vertical‐till. Manure injection increased N2O and CO2 emissions, with the magnitude of this effect being greatest for 1 mo post‐application. Manure injection also increased soil ammonium and nitrate but did not increase yield or crop quality relative to broadcast application. Similarly, tillage did not affect crop yield or protein content. Despite the tradeoffs between mineral N retention and elevated GHG emissions, manure injection in no‐till systems benefits farmers by reducing soil carbon losses as CO2, retaining mineral N, and maintaining crop yields and quality.